Foaming behaviour of primary, secondary and tertiary aqueous solution of amine for the removal of carbon dioxide - Wan Nur Atikah, Ali (2014)
This study is focusing on the effect by the usage of different amine in order to remove acid gases that is foaming. Foam is made up of thousands of gas filled bubbles. Bubbles are formed when a liquid film encapsulates gas. This research is to investigate the foaming behaviour on the different cases for the primary (monoethanolamine, MEA), secondary (diethanolamine, DEA) and tertiary (methyldiethanolamine, MDEA) amine on the effect of concentration, temperature and impurities. Effect of all this parameters will be evaluated based on height of foam and collapse time of foam. Nitrogen gas (N2) will be used in this experiments as bubble gas. For this work several hypothesis has been set according to respectively cases. The hypothesis of this study is a higher solution concentration of MEA will reduce the foaminess. Other hypothesis is a higher solution temperature of MEA and DEA will reduce the foaminess also. Effects of impurities toward foaming formation are classified as following: iron sulphide, for MDEA solution foaming decrease; sodium chloride, for MDEA solution tendency for formation of foam decrease; methanol, foaming decrease in MDEA solution. It is apparently iron sulphide meet the most influential contaminants to the foam formation at the same concentrations of all impurities studied